LITERASI NUMERASI DALAM PERSPEKTIF AL-KHWARIZMI: INTEGRASI ILMU MATEMATIKA DAN NILAI-NILAI ISLAM - Sabrina, Ainah; Alwizar, Alwizar; E. Hulawa, Djeprin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
This article aims to examine numeracy literacy from the perspective of Al-Khwarizmi's thoughts and how the integration between mathematics and Islamic values can be built in the context of contemporary education. This study uses a library research method by reviewing various scientific literature, both in the form of books and journals that are relevant in the last four years. The results of the study show that Al-Khwarizmi's thoughts not only provide a strong foundation for the development of modern mathematics, but also contain Islamic spiritual and ethical values that are relevant in the formation of value-based numeracy literacy. The integration between mathematical logic and Islamic principles can be an alternative holistic educational approach, especially in developing the character and critical thinking skills of students in a balanced manner.